FEATURES OF FINANCIAL BEHAVIOR IN CASH, CARDS AND APPLICATIONS - Hayrapetyan, Davit; Petrosyan, Nvard (Modern Psychology, 2023)
Nowadays market develops new means of payment to force consumers increase their spending readiness. New means of paying (different applications and cards) decrease ‘‘pain of paying’’ and increase readiness of spending. But different means of paying are differently perceived and accepted by the consumers. This research is aimed to reveal some features of spending and financial behavior of consumers depending their preference of cash, cards and applications. Our earlier research proves that using of cash depends on the age. The older persons prefer cash. In certain payments the youngest group prefers doing payments by applications. Unemployed people are more tended to choose cash spending. Those, who generally preferred paying in cash or card, noted that utility bills are paid by app. So, if well-working and trusted system exists people choose application. Reason can be either consumers tend to focus less on the negative feeling associated with the amount paid or with absence of queues and general easiness. Now we tried to discover online consuming features and some psychological characteristics depending of preferences of different means of payment.